Effects of starting weight, body condition, and age on gain of cattle grazing native grass - F.K. Brazle; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1999)
In 29 trials over 10 years, 6,614 head of cattle (heifers - 11 trials, 2,862 hd; steers - 18 trials, 3,752 hd) were used to determine the effect of starting weight on gain while grazing burned, native-grass pastures. The heifers grazed for an average of 81 days (70 to 93) and steers for an average of 86 days (75 to 99) from April to July. Stocking rate was one animal per 2 acres. The cattle were sorted by starting weight into groups as follows: below 399 lb, 400 to 499 lb, 500 to 599 lb, 600 to 699 lb, and above 700 lb. In three other trials, 613 yearling heifers were sorted by starting weight, as shown above, and assigned a body condition score from 1 (thinnest to 5 (fattest). A separate grazing trial was conducted in which 158 yearling steers were compared to 103 steer calves. The yearlings were spring born and wintered on wheat pasture; the calves were fall born. Lightweight heifers had the greatest daily gain. Heifers between 400 and 499 lb gained considerably more (P<.08) than heifers that weighed more than 600 lb. The steers with starting weights between 400 to 499 lb and 500 to 599 lb gained substantially more (P<.01) than other weight groups. Steers gained faster than heifers (2.29 lb vs 1.90 lb/day, P<.01). As heifers became fleshier, gain declined in all weight groups. Fall-born steer calves (444 lb) gained slower (2.45 vs 2.68 lb per day, P<.01) than spring-born yearling steers (587 lb). Based on these data, the optimum starting weight for stocker cattle is between 400 and 499 lb for heifers and between 400 and 599 lb for steers. Yearling steers gained better than calves. In conclusion, sex, age, and starting weight of cattle affect their gains while grazing burned, native grass pastures. The optimum weight for best pasture gain may vary by forage type and quality, but clearly there is an ideal weight range for stocker cattle used for grazing.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Stocker; Starting weight; Grass